Peran Pekaseh Dalam Pelestarian Budaya Subak Di Bali - I Wayan Sudika (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Preservation of Subak existence in Bali as one of the local genius must be done by all stakeholders. Pekaseh is a Prajuru Subak, who is managing Subak in general, assisted by Pangliman, Penyarikan, Kasinoman, Patengen and Kelihan Tempek. As a leader, Pekaseh has a strategic to role participate in trying to keep Subak's existence, both in Parhyangan, Pawongan, and Palemahan aspects. However, Pekaseh in assignment to preserve Subak culture, Pekaseh usually encounters principal constraints resulting from the character of most societies today which is empirical-profane materialistic, which causes: (a) Society is very easy to sell land for a lot of money. (b) Granting land transfer permits for housing, without coordinating with the Pekaseh. (c) The interest of the younger generation to become farmers is very little. The young generation prefers to work in other sectors such as the more promising tourism sector. (d) Society today cannot be separated from materials or money, so most people's lives are pursuing materials/money.Keyword: Pekaseh, Subak